An empirical examination of UTAUT model and social network analysis. Issue 1 (2nd December 2019) - Xu, Zhaoyi; Li, Yingtong; Hao, Liuchang
Abstract : Purpose: The purpose of this paper is to ensure the sustainability of the competitive advantages of internet financial enterprises. In recent years, driven by the two wheels of financial market and information technology, the internet finance has experienced an extremely rapid development. Design/methodology/approach: Based on the performance expectation, effort expectation, social influence and purchase intention of UTAUT model, an empirical examination was conducted. Specifically, the authors made the user purchasing behavior as the dependent variable and added some new factors such as perceived risk, individual innovation and product cognition as the independent variables in the model, and they also added user gender and experience as regulated variables, so as to study the impact factors that affect the purchasing behavior. In addition, the authors also studied the impact of social network friend recommendations on consumers' willingness to purchase. Findings: The research results showed that effort expectation, performance expectancy, effort expectancy, purchase intention, awareness and individual innovation have a positive effect on the behavior of buying financial products, whereas the perceived risk has a negative effect on the behavior of buying internet financial products. Additionally, in the context of social networking, social network friend recommendations have a positive impact on consumers' willingness to purchase. Research limitations/implications: This paper is based on the integrated technology acceptance model, which makes the user purchasing behavior as the dependent variable and adds some new factors such as perceived risk, individual innovation and product cognition as the independent variables. However, the research on recommendation between social network friends is not deep enough, so further improvement is needed. Practical implications: This study can enrich the existing theories on the interpretation of the intention of using internet financial products, help internet financial enterprises understand user behavior and demands better, and improve service quality and customer satisfaction. Originality/value: This study provides an empirical examination of UTAUT model and social network analysis.